Increasing Legal Culture Of Students By Improving The Teaching Of Criminal Law - Khamrakulov Zafarjon Yigitalievich (Peerian Journals Publishing, 2022)
the article highlights the issues of increasing the legal literacy of students by improving the teaching of criminal law in educational institutions. The article also provides statistical data on crimes, their origin and recommendations for the prevention of offenses.
Keywords: criminal law; legal literacy; young generation; crime